Newcastle Disease Virus Displaying an Ectodomain of Middle East Respiratory Syndrome Coronavirus Spike Protein Elicited Robust Humoral and Cellular Immunity in Mice - Jaturawitt Prasopsiri; Kanjana Srisutthisamphan; Benjamas Liwnaree; Juggragarn Jengarn; Jarin Kramyu; Payuda Hansoongnern; Papon Muangsanit; Nathiphat Tanwattana; Challika Kaewborisuth; Suttipun Sungsuwan; Anan Jongkaewwattana; Nanchaya Wanasen (Vaccines)
Background: Middle East Respiratory Syndrome Coronavirus (MERS-CoV) causes severe respiratory illness in humans and currently lacks an approved vaccine. The Newcastle disease virus (NDV) vector is a well-established, safe, and effective platform for vaccine development. With recent advancements in stabilizing coronavirus spike proteins to enhance their antigenicity, this study aimed to determine whether modifications to the MERS-CoV spike protein could improve its presentation on NDV particles, allowing the resulting virus to be used as an inactivated vaccine. Methods: We codon-optimized the gene encoding the ectodomain of the MERS-CoV spike protein and incorporated modifications at the S1/S2 and S2’ cleavage sites, along with a proline substitution at residues V1060-L1061. This modified spike gene was inserted into the NDV genome to create the NDV-SMERS virus. After purification and inactivation, the vaccine’s immunogenicity was assessed in mice. Results: Mice immunized with the inactivated NDV-SMERS vaccine developed robust anti-spike IgGs, neutralizing antibodies, and cellular immune responses. The study demonstrated that modifications to the MERS-CoV spike protein were essential for its effective presentation on NDV particles. Additionally, the spike gene insert remained stable through five egg passages, confirming the vector’s stability. Conclusions: Engineering the MERS-CoV spike protein is crucial for its successful display on NDV particles. The strong immune responses elicited by the NDV-SMERS vaccine in mice highlight that NDV is a promising, safe, and effective platform for MERS-CoV vaccination.